2020
DOI: 10.1584/jpestics.d20-028
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic basis for synergism of 2,4-D amine and metribuzin in <i>Avena sterilis</i>

Abstract: The combination of herbicides with different modes of action has been adopted not only to improve weed control but also to increase the environmental sustainability of plant-protection products. In this study, we showed a synergistic effect of the auxin herbicide 2,4-D amine with the PSII-inhibiting herbicide metribuzin to control the global grass weed wild oat (Avena sterilis) population and investigated the underlying mechanisms. Pretreatment with 2,4-D amine did not change the foliar absorption of metribuzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The 14 C-halosulfuron translocation in treated leaves of corn (Zea mays L.) was 96% [31]. In contrast, the 14 C-metribuzin translocation was limited in wild oat (Avena Sterilis L.) [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 14 C-halosulfuron translocation in treated leaves of corn (Zea mays L.) was 96% [31]. In contrast, the 14 C-metribuzin translocation was limited in wild oat (Avena Sterilis L.) [32].…”
Section: Discussionmentioning
confidence: 99%
“…The 14 C-halosulfuron translocation in treated leaves of (Zea mays L.) was 96% [31]. In contrast, the 14 C-metribuzin translocation was limit wild oat (Avena Sterilis L.) [32]. Choice of appropriate rates and tank-mix partner(s) is critical for weed control.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mixture resulted in enhanced metribuzin translocation to the roots and new leaves. Since new leaves express high levels of the psbA gene to prepare this nascent tissue for photosynthesis, the synergism is most likely due to the increased metribuzin translocation to new leaves, even though enhanced metabolism may offset some of the effect (Han et al, 2020).…”
Section: Physicochemical Incompatibilitymentioning
confidence: 99%
“…All other interactions were additive (Table 4). Han et al (2020) found that sequential applications of 2,4-D amine followed by metribuzin caused a synergistic interaction with increased metribuzin movement to the newly developed leaves in wild oats [Avena sterilis (L.)]. In corn, the co-application of 2,4-D with atrazine, a photosystem II-inhibitor, resulted in a synergistic improvement in the control of prostrate knotweed [Polygonum aviculare (L.); Ludwig 1973].…”
Section: Soybean Injurymentioning
confidence: 99%